Geophysical survey (Scottish Historical and Archaeological Internet Reports, 2003)
Capo long barrow is covered with tree stumps and bracken so was considered unsuitable for a geophysical radar survey. A detailed account of the method of resistivity imaging is provided. A total of 48 profile views were taken along with plan views. Profiles taken to the east of the long barrow in front of the presumed entrance and over the low mound proved to be inconclusive.